2015
DOI: 10.1098/rspb.2015.1553
|View full text |Cite
|
Sign up to set email alerts
|

Orchid phylogenomics and multiple drivers of their extraordinary diversification

Abstract: Orchids are the most diverse family of angiosperms, with over 25 000 species, more than mammals, birds and reptiles combined. Tests of hypotheses to account for such diversity have been stymied by the lack of a fully resolved broad-scale phylogeny. Here, we provide such a phylogeny, based on 75 chloroplast genes for 39 species representing all orchid subfamilies and 16 of 17 tribes, time-calibrated against 17 angiosperm fossils. A supermatrix analysis places an additional 144 species based on three plastid gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

69
541
12
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 398 publications
(625 citation statements)
references
References 45 publications
69
541
12
3
Order By: Relevance
“…2). The result indicated that L. loeselii is clustered together with D. officinale what confirmed close relationship of Liparis and Dendrobium genera reported in Givnish et al (2015). The complete plastid genome information reported in this paper provided data useful for population genomic studies, conservation works on L. loeselii as well as for phylogenetic studies within Orchidaceae.…”
supporting
confidence: 60%
“…2). The result indicated that L. loeselii is clustered together with D. officinale what confirmed close relationship of Liparis and Dendrobium genera reported in Givnish et al (2015). The complete plastid genome information reported in this paper provided data useful for population genomic studies, conservation works on L. loeselii as well as for phylogenetic studies within Orchidaceae.…”
supporting
confidence: 60%
“…The answer is most likely both. Givnish et al (2015) showed that Pleurothallidinae has one of the highest species diversification rates in the Orchidaceae. With just above 10 My of age, the subtribe is about one third younger than Laeliinae and Oncidiinae and has more than double the number of species.…”
Section: Uncertain Affinitiesmentioning
confidence: 99%
“…A number of studies have taken advantage of this technology, using either chloroplast protein-coding genes (e.g. Givnish et al 2015;Washburn et al 2015;Barrett et al 2016) or complete chloroplast genomes (e.g. Carbonell-Caballero et al 2015;Cotton et al 2015;Burke et al 2016;McKain et al 2016b) to resolve phylogenetic relationships from as deep as across Viridiplantae (Ruhfel et al 2014) to within a species complex (e.g.…”
mentioning
confidence: 99%